2022
DOI: 10.3390/jcm11092401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COVID-19 Spread in Tokyo through an Agent-Based Model with Data Assimilation

Abstract: In this paper, we introduce an agent-based model together with a particle filter approach to study the spread of COVID-19. Investigations are mainly performed on the metropolis of Tokyo, but other prefectures of Japan are also briefly surveyed. A novel method for evaluating the effective reproduction number is one of the main outcomes of our approach. Other unknown parameters are also evaluated. Uncertain quantities, such as, for example, the probability that an infected agent develops symptoms, are tested and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The spatial and temporal scales of these models varied considerably. These models studied the infection spread over a variety of geographical locations ranging from a large building (school or hospital) to a country and the temporal scales of the modelling outcomes range from a couple of weeks to several months [34][35][36][37][38][39][40][41][42][43][44][45][46]. Agent-based modelling tools such as Covasim [29] and PanSim [33] have been used to model infection spread in cities and countries over a period of a year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and temporal scales of these models varied considerably. These models studied the infection spread over a variety of geographical locations ranging from a large building (school or hospital) to a country and the temporal scales of the modelling outcomes range from a couple of weeks to several months [34][35][36][37][38][39][40][41][42][43][44][45][46]. Agent-based modelling tools such as Covasim [29] and PanSim [33] have been used to model infection spread in cities and countries over a period of a year.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological models of COVID-19 infection have been developed using agent-based modelling approach to investigate various non-pharmaceutical intervention strategies such as social distancing, usage of masks, contact tracing and subsequently these models also explored the spatial aspects of infection spread [26][27][28][29][30][31][32][33]. Particularly, it is used to investigate various levels of interaction details of the infection propagation in healthcare facilities [34,35], educational institutions [36][37][38][39], cities [40][41][42], states and countries [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…They found that to minimize COVID-19-related hospitalizations and deaths, elderly and vulnerable persons should be prioritized for vaccination until further vaccines are available. Sun et al [49] introduced an agent-based model together with a particle filter approach as a method for studying the evolution of COVID-19. With this model, they introduced a novel method for evaluating the effective reproduction number.…”
Section: Abms In Epidemic Modelingmentioning
confidence: 99%
“…This formula indicates that as state dimensionality grows, particle requirements increase exponentially. Moreover, particle filters have seen applications in traffic estimation [66] and epidemiology [67,68], among others. In epidemiology, [69] initiated the application of particle filters, while [70] introduced the Smart Beam Particle Filter (SBPF) for epidemic forecasting.…”
Section: Particle Filtermentioning
confidence: 99%